THE RELATIONSHIP BETWEEN DYSMENORRHEA KNOWLEDGE AND DYSMENORRHEA HANDLING BEHAVIOR IN YOUNG WOMEN AT SMAN 1 TAMBUN UTARA IN 2022 - Fauziah, Siva; Dinda Nur Fajri Hidayati Bunga; Kiki Deniati (Soscience: Jurnal Ilmu Sosial Science, 2024)
Many young women ignore pain during menstruation. Dysmenorrhea has a bad impact on young women, namely causing disturbances in teaching and learning activities, not paying attention to the explanations given by the teacher, and the tendency to sleep in class during teaching and learning activities. Health conditions during menstruation are influenced by the level of knowledge. A person with insufficient knowledge will tend to ignore health and in the end, he will have dangerous actions for himself. research Objectives:To determine the relationship between knowledge about dysmenorrhea and behavior in handling dysmenorrhea in adolescent girls at SMAN 1 Tambun Utara in 2022. Research Methods: The design in this study was Analytical Observation with a Cross-Sectional research design, using the independent variable knowledge of dysmenorrhea and the dependent variable handling behavior, the sampling technique in this study is probability sampling type simple random sampling with a sample of 205 respondents. The instrument in this study used a digital questionnaire and statistical tests were carried out using Chi-Square. Research Results: Based on the output of the chi-square statistical test, the Asymp Significance value is 0.000. It can be concluded that the Asymp Significance value (0.000) < value (0.05), indicates that H0 is rejected. Thus it can be interpreted that "the relationship of knowledge about dysmenorrhea with behavior in handling dysmenorrhea in adolescent girls at SMAN 1 Tambun Utara in 2022. Conclusion: There is a relationship between knowledge about dysmenorrhea and behavior in dealing with dysmenorrhea in adolescent girls at SMAN 1 Tambun Utara in 2022.